Hubungan Strategi Koping dengan Kualitas Hidup Ibu yang Memiliki Anak Disabilitas Intelektual: The Relationship between Coping Strategies and Quality of Life of Mothers with Children with Intellectual Disabilities - Nur Lu’lu’atul Ahadiah; Liyanovitasari (Journal of Holistics and Health Sciences, 2024)
Intellectual disability is a child whose development of intellectual function experiences obstacles accompanied by disabilities in learning and adjusting, which can make parents need special handling and also result in increased burden and stress that can affect the quality of life. A factor affecting the quality of life of the family is coping strategies. The purpose of this study was to determine the relationship between coping strategies and the quality of life of mothers who have children with intellectual disabilities. This research design is descriptive correlational with a cross sectional approach. The population is parents who have children with intellectual disabilities at Ungaran State Special School with a consecutive sampling technique of 64 respondents. The measuring instrument used is a questionnaire. The data analysis used is the chi square test. Results: Most respondents had adaptive coping strategies with a moderate maternal quality of life, which was 32 respondents (78.0%). There is a relationship between coping strategies and the quality of life of mothers who have children with intellectual disabilities. With p value = 0.000 < α (0.05). Suggestion: Parents can improve coping strategies by planning everything about their children, can also control stress well so that it does not interfere with daily activities, for example by cultivating feelings of optimism, always getting closer to God Almighty and always praying.   ABSTRAK Disabilitas intelektual adalah anak yang perkembangan fungsi intelektualnya mengalami hambatan yang disertai ketidakmampuan dalam belajar dan menyesuaikan diri, sehingga dapat membuat orang tua membutuhkan penanganan khusus dan juga mengakibatkan peningkatan beban dan stres yang dapat mempengaruhi kualitas hidup. Faktor yang mempengaruhi kualitas hidup keluarga adalah strategi koping. Tujuan penelitian ini adalah mengetahui hubungan strategi koping dengan kualitas hidup ibu yang memiliki anak disabilitas intelektual.  Desain penelitian ini diskriptif korelasional dengan pendekatan cross sectional. Populasi adalah orang tua yang memiliki anak disabilitas intelektual di Sekolah Luar Biasa Negeri Ungaran sejumlah 87 responden, dan sampel sejumlah 64 responden dengan teknik consecutive sampling. Alat ukur yang digunakan kuesioner. Analisis data yang digunakan adalah uji chi square.  Sebagian besar responden memiliki strategi koping adaptif dengan kualitas hidup ibu kategori sedang yaitu sebanyak 32 responden (78.0%). = Ada hubungan strategi koping dengan kualitas hidup ibu yang memiliki anak disabilitas intelektual. Dengan nilai p value = 0,000 < α (0,05). Orang tua dapat meningkatkan strategi koping dengan merencanakan segala sesuatu mengenai anaknya, juga dapat mengendalikan stres dengan baik sehingga tidak mengganggu aktifitas sehari-hari, misalnya dengan menumbuhkan perasaan optimis, selalu mendekatkan diri kepada Tuhan Yang Maha Esa dan selalu berdo’a.